KAIDAH DASAR MANAJEMEN PENDIDIKAN ISLAM MENURUT PERSPEKTIF QUR’AN DAN HADITS - Sri Putrianingsih; Putra, Thoha (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2024)
The Holy Qur'an contains everything related to the existence and dynamics of human life as creatures in the universe. Including the discussion of the history of the origin of human creation by the creator to the activities carried out by humans. One of them is about education management. In this case because the holy book al quranul karim is the main teaching of Islam whose function is as a guide for mankind so that mankind becomes a good and right